Uso de recursos multimedia para potencializar el grado de interactividad, participación y aprendizaje de los estudiantes del octavo año de educación básica de la Unidad Educativa Réplica Eugenio Espejo de la ciudad de Babahoyo Provincia Los Ríos - Larenas Vera, Alvaro Antonio (2022)
Currently the educational process has had a significant change in terms of technology, today the digital age is an important contribution to the benefit of learning, taking into account that education is a personal process that facilitates the comprehensive development of faculties of an individual and the taste for knowing. It has been shown that the use of traditional methods becomes a monotonous and boring learning process for students in the eighth year of basic education of the Eugenio Espejo Replica Educational Unit, and sometimes the teacher fails to capture the student's attention and it is difficult to its interaction in the classroom. That is why information and communication technologies (ICT) play an important role in meeting human needs. Using in many cases the computer as a means of support for computer tools that generate suitable products for the new demands of the educational labor market and help the student to assume a leading role in the changes of this century. In addition, through the use of multimedia resources the teacher has the facility to motivate the student to interact, participate and in turn evaluate the learning of the students in the eighth year of basic education of the Replica Eugenio Espejo educational unit.